How Organizational Trust and Commitment Impact Performance - Rustianah; Ardianto, Riski Eko; Hasyim, Wachid (Jurnal Multidisiplin Madani, 2024)
Human resources (HR) are the main component in an organization, and also Human resources have an important role in every activity and activity implementation carried out by an organization. To improve employee performance, several things that need to be considered are issues of organizational trust and commitment. The research uses quantitative research methods using primary data collected through online questionnaires. The population in this study was 200 active employees who worked at one of PT. Module Intrac Yasatama and the sample used was 90 respondents. The data was  analyzed using multiple linear regression analysis techniques. Based on research results, organizational trust and commitment has a positive and significant effect on employee performance